The pearl - Steinbeck, John, 1902-1968. (New York : Penguin Books, 1992)
Terrible events follow the discovery of a magnificent pearl by a poor Mexican fisherman.
Originally published: 1945.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
6.5.
6.5
Keywords: Fishers; Pearls -- Fiction; Fishers; Pearls -- Fiction; Mexico -- Fiction; Mexico -- Fiction